A study on the relationship between personality and motivation in leisure participants - Gül Yağar; Gamze Deryahanoğlu; Emine Bal (PLoS ONE, 2025)
Motivation and personality, which are among the most important effects of human behavior, are important in terms of leisure activities. Therefore, this study aimed to examine the relationship between motivation and personality of individuals who participate in physical activity in their leisure time. In the study, the correlational screening model was used, and 370 (m:28.76±10.37) participants who regularly practiced physical activity participated. The relationship between the data obtained in the research was tested with canonical correlation analysis, and the first two canonical correlation functions between the two variable data sets were interpreted. Self-control and extraversion sub-dimensions in the personality data set and internal regulation and external regulation sub-dimensions in the motivation data set were found to make the highest contribution. It was determined that for the first set of canonical functions, the relationship between self-control and internal regulation had a unidirectional correlation, whereas, for the second set of canonical functions, the relationship between extraversion and external regulation had an inverse correlation. Studies show how valuable intrinsic motivation sources are for individuals, and personality traits such as self-control and extraversion support this situation. It is considered that the personality traits of leisure time participants may be a clue to the types of motivation of the participants.